The successful management for long-term intractable enteroatmospheric fistula: A case report - Tatsuta, Kyota (Ann Med Surg (Lond), 2020)
INTRODUCTION: Efficacy of open abdomen management with negative pressure wound therapy for enteroatmospheric fistula has been performed. But, few reports have shown its utility for enteroatmospheric fistula several years after onset. PRESENTATION OF CASE: A 46 year-old woman underwent total colectomy due to total ulcerative colitis in her twenties. Three years before the onset of enteroatmospheric fistula, she underwent simple total hysterectomy for uterine smooth muscle tumor. Small bowel obstruction occurred early and a small bowel bypass was performed. However, she had sudden abdominal pain and was diagnosed with anastomotic leakage of small bowel bypass. Although antibiotic treatment was initiated, infection was difficult to control, and a midline abdominal incision was performed, followed by the formation of enteroatmospheric fistula. She declined early surgical intervention and started receiving home parenteral nutrition with antibiotic treatment. Although central vein management was continued, catheter infection became frequent. Hence, surgical intervention was planned 30 months after the formation of enteroatmospheric fistula. Two-stage abdominal wall reconstruction using open abdomen management with negative pressure wound therapy was planned. The definitive abdominal wall reconstruction was performed 14 days after the initial operation. Finally, she was discharged without reoperation. DISCUSSION: Enteroatmospheric fistula has no overlying soft tissue and no real fistula tract. Besides these complications, there were complications of the scarred abdominal wall from intestinal fluid exposure for 30 months. CONCLUSION: The strategy using open abdomen management with negative pressure wound therapy for long-term enteroatmospheric fistula will have a good postoperative outcome with the same as early intervention.